1995
DOI: 10.1083/jcb.130.1.227
|View full text |Cite
|
Sign up to set email alerts
|

A targeted mutation at the known collagenase cleavage site in mouse type I collagen impairs tissue remodeling.

Abstract: Abstract. Degradation of type I collagen, the most abundant collagen, is initiated by collagenase cleavage at a highly conserved site between Gly775 and I1e776 of the od(I) chain. Mutations at or around this site render type I collagen resistant to collagenase digestion in vitro. We show here that mice carrying a collagenaseresistant mutant Colla-1 transgene die late in embryogenesis, ascribable to overexpression of the transgene, since the same mutation introduced into the endogenous Colla-1 gene by gene targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
243
1
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(253 citation statements)
references
References 54 publications
(64 reference statements)
8
243
1
1
Order By: Relevance
“…However, there is evidence to suggest that fibrotic scenarios develop in mice if MMP activity is reduced. Mice with a targeted mutation in the collagenase cleavage site in the collagen type I molecule 54,55 show a number of alterations in tissue remodeling, reflecting the inability to degrade type I collagen, including a thickening of the dermis and fascia similar to fibrin-injected skin in the present study. Haraguchi and colleagues 56 showed that when rats with experimental glomerulonephritis were treated with recombinant tPA, a significant increase in plasmin was observed that resulted not only in reduced fibrin deposition but also a significant increase in MMP activation and a concomitant reduction of collagen accumulation in the glomeruli.…”
Section: Discussionmentioning
confidence: 64%
“…However, there is evidence to suggest that fibrotic scenarios develop in mice if MMP activity is reduced. Mice with a targeted mutation in the collagenase cleavage site in the collagen type I molecule 54,55 show a number of alterations in tissue remodeling, reflecting the inability to degrade type I collagen, including a thickening of the dermis and fascia similar to fibrin-injected skin in the present study. Haraguchi and colleagues 56 showed that when rats with experimental glomerulonephritis were treated with recombinant tPA, a significant increase in plasmin was observed that resulted not only in reduced fibrin deposition but also a significant increase in MMP activation and a concomitant reduction of collagen accumulation in the glomeruli.…”
Section: Discussionmentioning
confidence: 64%
“…This substrate was prepared from tails of transgenic mice bearing a targeted collagen mutation at collagenase-1 cleavage site. The mutation constitutes a substitution of 3 amino acids at the collagenase cleavage site of the ␣1(I) collagen chain (30,31). As shown in Fig.…”
Section: Fgf-2 Stimulation Does Not Enhance Migration Of Smcs Onmentioning
confidence: 99%
“…However, it has been much more challenging to study substrate cleavage by MMPs in vivo, largely due to the difficulty of detecting the cleaved products. A combination of molecular, genetic, and cell biological studies have provided strong evidence to support the cleavage of type I collagen by collagenase 1 (MMP1) or other collagenases in vivo (Wu et al, 1990;Liu et al, 1995;Pilcher et al, 1997). In addition, by using mouse deficient in matrilysin (MMP7), the intestinal paneth cell ␣-defensins (cryptdins) and epithelial cell surface-bound proteoglycan syndecan-1 were identified as in vivo substrates of this MMP (Wilson et al, 1999;Li et al, 2002), aided in part by the formation of stable cleavage products.…”
Section: Cell Surface Lr Is An In Vivo Substrate Of St3mentioning
confidence: 99%